Germany - Kordel, Stefan; Weidinger, Tobias; Spenger, David (13 quantitative briefings on the case studies (= Deliverable D5.2 of MATILDE project), 2021)
Deliverable 5.2 - 13 quantitative briefings on the case studies, presents data collected in Task 5.2 in the 13 locations where the local case studies are implemented. Quali-Quantitative briefings cover both MATILDE Social Dimensions (MSDs) and MATILDE Economic Dimensions (MEDs). Specific attention has been paid to the impact of reception services for asylum seekers and refugee